The Integration of Audiovisual Media into the Islamic Religious Education Curriculum: Opportunities, Challenges, and Implications - Lubis, Indah Syafri; Sriwardona, Sriwardona; Mayanti, Desi; Sari, Melia (El-Rusyd, 2026)
This study aims to determine the effectiveness and role of audiovisual media in enhancing students’ understanding, motivation, and engagement in Islamic Religious Education. The method used is a qualitative approach employing content analysis, with data collection procedures involving a review of scientific articles and books (2010–2025). The analysis was conducted using thematic qualitative analysis to identify key findings regarding the benefits, challenges, and best practices of using audiovisual media in the context of Islamic Religious Education. The results indicate that audiovisual media enhance students’ understanding of religious concepts, memory retention, and learning motivation; reinforce the interpretation of religious values through visual and audio representations; and support differentiated instruction. Challenges include limitations in facilities and infrastructure, the quality of learning resources, and teachers’ readiness in developing audiovisual materials. The implications of this research include recommendations for the development of audiovisual materials based on the values of Islamic Religious Education, enhanced teacher training (technical and pedagogical competencies), and school policies for providing infrastructure and systematically integrating audiovisual media into the Islamic Religious Education curriculum to improve student learning outcomes and character.